Limited evidence for third-party affiliation during development in wild chimpanzees (Pan troglodytes schweinfurthii). Issue 9 (13th September 2017) - Miller, Jordan A.; Stanton, Margaret A.; Lonsdorf, Elizabeth V.; Wellens, Kaitlin R.; Markham, A. Catherine; Murray, Carson M.
Abstract : Examining the ontogeny of conflict-mitigating behaviours in our closest living relatives is an important component of understanding the evolutionary origins of cooperation in our species. In this study, we used 26 years of data to investigate the emergence of third-party affiliation (TPA), defined as affiliative contact given to recipients of aggression by uninvolved bystanders (regardless of initiation), in wild immature eastern chimpanzees ( Pan troglodytes schweinfurthii ) of Gombe National Park, Tanzania. We also characterized TPA by mothers in the same dataset as an adult benchmark for interpreting immature TPA patterns. In summary, we found that immatures did not express TPA as measured by grooming between the ages of 1.5 and 12.0 years, and that there was limited evidence that immatures expressed TPA via play. We also found that mothers did express TPA to offspring, although mothers did not show TPA towards non-offspring. Cases of TPA by mothers to other adults were too few to analyse separately. These results contrast with findings from captive studies which found that chimpanzees as young as 6 years of age demonstrated TPA. We argue that within-species variation in the expression of TPA, both in immatures and adulthood, provides evidence that the conflict management behaviours of young chimpanzees may be heavily influenced by social, ecological and demographic factors.